Sharia Hotels: Identifying the Substantive and Label-Based Elements of Sharia Compliance in Hotels in Pekalongan City - Isfandiar, Ali Amin; Rinda, Asytuti; Makarim, Ahmad Nabil (Hikmatuna : Journal for Integrative Islamic Studies, 2025)
The development of Sharia-based business practices can be examined from two opposed perspectives: the Sharia label and Sharia substance. This article aims to analyze and compare the implementation of the ten Sharia principles outlined in DSN-MUI Fatwa No. 108/DSN-MUI/X/2016, which provide guidelines for Organizing Tourism Based on Sharia Principles, within hospitality business entities, including both Sharia-compliant hotels and conventional hotels. These ten principles serve as the theoretical framework and basis for the interview guidelines in this qualitative study. Data were obtained from seven hotel managers who served as informants. This study concludes that the interaction between business practices and religious (Sharia) principles gives rise to three categories of hotels. First, fully Sharia, referring to hotel models that implement Sharia principles comprehensively. Second, partially Sharia, referring to hotel models that implement Sharia principles selectively. Third, limited Sharia refers to hotel models that apply Sharia principles to a limited extent. Several factors influence these three categories: (1) internal rules or policies of the owners; (2) market or customer characteristics; (3) central and local government regulations; and (4) the Indonesian Hotel and Restaurant Association (PHRI). The urgency of this research lies in demonstrating that Sharia compliance does not always need to be expressed through a formal label; it may also be realized through substantive practices, which are more universally acceptable. Empirical evidence shows, first, that Sharia-labeled business practices are far fewer in number than those without such a label, and second, that upon closer and more profound observation, many unlabeled business practices are already Sharia-compliant. This phenomenon is referred to as substantive Sharia.